The evaluation of the usage of cigarette and alcohol among the students of physical education and sports high school department of gazi university - Yılmaz, Gürkan; İbiş, Serkan; Sevindi, Tarık (Journal of Dependence, 2007)
Objective: This study has been done to determine the frequency and risk factors of the usage of cigarette and alcohol among the students of Physical Education and Sports High School Department of Gazi University.Method: The study has been done on 200 students of Physical Education and Sports High School Department of Gazi University. The frequency of the usage of cigarette and alcohol, the behaviours related to the usage of cigarette and alcohol and its effects on family members have been investigated.The statistical analysises has been done by SPSS 11.00.Results: We determined that; the frequency of smoking cigarette is %53.0,non smoker frequency is %47.0 ,%25.0 of the smokers smoke 12-17 cigarettes a day, %25.0 of them have started by the effect of their friends, %25.0 of them started to smoke at the age of 16-20. We determined that the %88.3 of the smokers’ parents also smoke. The frequency of drinking alcohol is %60.0, nondrinker frequency is %40.0, %23.0 of the drinkers drink 3-5 glasses a day, %27 of them started to drink because of affectation, %25.0 have started to drink at the age of 16-20, %94.7 of the mothers’ and %87.5 fathers’ of these drinkers also drink alcohol.Conclusion: It has been understood that the usage of cigarette and alcohol among the students of Physical Education and Sports High School Department of Gazi University is very high and the addiction of cigarette and alcohol effects the members of a family. It can also be said that getting bad habits is effected by closer society.
Keywords: Cigarette; alcohol; university students; model